Association of Age-Related Trends in Blood Pressure and Body Composition Indices in Healthy Adults - Li, Wei; He, Yan; Xia, Lili; Yang, Xinghua; Liu, Feng; Ma, Jingang; Hu, Zhiping; Li, Yajun; Li, Dongxue; Jiang, Jiajia; Shan, Guangliang; Li, Changlong (Frontiers in Physiology, 2018)
Purpose: Adiposity is one of the important determinants of blood pressure. The aim of this study is to evaluate the association between blood pressure and body composition indices throughout the whole lifespan of healthy adults. Patients and methods: This study was from an ongoing cross-sectional survey of the Chinese health wherein data included basic physiological parameters. Partial Pearson correlation analysis was used to assess the correlation between blood pressure and body composition indices. Multiple linear regression analysis was used to assess the association of body mass index, lean mass percent and visceral fat rating against blood pressure in each age group. Results: In the whole population stratified by gender, while body mass index had the highest r-value of correlation with systolic blood pressure in both males (r=0.296, p<0.001) and females(r=0.237, p<0.001), and fat mass percent had the highest r-value of correlation with diastolic blood pressure in males (r=0.351, p<0.001) and females(r=0.277, p<0.001), the strength of association with blood pressure were similar across most of the body composition indices. In multiple linear regression analysis, both body mass index and visceral fat rating were positively while lean mass percent was negatively associated with blood pressure in all age groups in both genders, whereas all the association was weaker in the elderly compared to the younger. Conclusion:Maintain the total body fat in a favorable range and appropriately increase the body muscle mass is a strategy to reduce the occurrence of cardiovascular event by decreasing the risk of hypertension through the whole adult life.